2007
DOI: 10.1128/jvi.01585-06
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A (IgA) Is a Natural Ligand of Hepatitis A Virus Cellular Receptor 1 (HAVCR1), and the Association of IgA with HAVCR1 Enhances Virus-Receptor Interactions

Abstract: The hepatitis A virus (HAV) cellular receptor 1 (HAVCR1/ TIM1) is a type 1 integral membrane glycoprotein consisting of a characteristic six-cysteine immunoglobulin (Ig)-like domain extended above the cell surface by a mucin-like domain that contains a variable number of threonine, serine, and proline (TSP) hexameric repeats (19). The monkey (19) and human (13) HAVCR1/TIM1 were the first identified members of the T-cell immunoglobulin mucin (TIM) family, an immunologically important group of receptors (22,28,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 52 publications
(75 reference statements)
0
26
0
1
Order By: Relevance
“…It was reported that an antibiotic resistance titration assay (ARTA) is useful for HAV neutralization including virus‐receptor interaction 33,34 . We also tested the effects of amantadine against HAV IRES of clinical isolates and confirmed the effects against fulminant hepatitis clones.…”
Section: Resultsmentioning
confidence: 70%
“…It was reported that an antibiotic resistance titration assay (ARTA) is useful for HAV neutralization including virus‐receptor interaction 33,34 . We also tested the effects of amantadine against HAV IRES of clinical isolates and confirmed the effects against fulminant hepatitis clones.…”
Section: Resultsmentioning
confidence: 70%
“…Previous reports have shown that TIM-1 is expressed on several different cell types, including activated CD4 T cells (4, 5) and mast cells (62), and that several different ligands have been proposed for TIM-1, including TIM-1 itself, TIM-4, and IgAl (30, 54, 63, 64). In man, TIM-1 is also the receptor for the hepatitis A virus (65), and infection with hepatitis A virus has been shown to reduce greatly the likelihood of developing asthma and allergy (66, 67).…”
Section: Discussionmentioning
confidence: 99%
“…Apical to basolateral transcytosis of HAV, mediated by the polymeric immunoglobulin receptor, has been shown to occur in polarized epithelial MDCK cells, and a similar IgA-mediated mechanism may be used by HAV in gut epithelia to achieve access to the circulation (19). IgA is a natural ligand of HAVCR1, and the association of IgA with HAVCR1 enhances virus-receptor interactions (63). It is of note, however, that virions would have to avoid uncoating in susceptible enteric cells in order to reach the bloodstream intact for transmission to the liver, and virus-specific IgA would need to have survived along with the virus in the environment (and the gut) to effect this function.…”
Section: Discussionmentioning
confidence: 99%